2006
DOI: 10.1111/j.0083-8703.2006.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics and Triple Eradication Therapy on the Cyclooxygenase (COX)‐2 Expression, Apoptosis, and Functional Gastric Mucosal Impairment in Helicobacter pylori‐Infected Mongolian Gerbils

Abstract: H. pylori infection in gerbils, associated with regenerative hyperplasia of glandular structure, results in the suppression of gastric secretion, overexpression of COX-2, and enhancement in apoptosis and impairment of both, gastric blood flow and gastrin-somatostatin link that were reversed by anti-H. pylori triple therapy and attenuated by probiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 48 publications
3
18
0
Order By: Relevance
“…Numerous studies have shown that apoptotic cell death of gastric mucosal cells has an important role in GML (18)(19)(20). In line with this, the present study found that the expression of Bax, caspase-3 and caspase-7 was higher in the stomach tissues of HAPC-induced GML patients than that in the healthy controls, suggesting that cell apoptosis also takes an active part in HAPC-induced GML.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous studies have shown that apoptotic cell death of gastric mucosal cells has an important role in GML (18)(19)(20). In line with this, the present study found that the expression of Bax, caspase-3 and caspase-7 was higher in the stomach tissues of HAPC-induced GML patients than that in the healthy controls, suggesting that cell apoptosis also takes an active part in HAPC-induced GML.…”
Section: Discussionsupporting
confidence: 90%
“…These include interleukin 8 and tumour necrosis factor α, which have been reported to increase gastrin expression. H pylori also activates gastrin releasing peptide (through the type IV secretion system) and regulates the gastrin modulator somatostatin to increase gastrin expression 38 39…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 was upregulated in atherosclerotic lesions [101] and catalyzes the production of the majority of vascular prostanoids in human atherosclerotic areas [102]. Down-regulated COX-2 was found in helicobacter pylori-infected mongolian gerbils with a commercial probiotic Lacidofil treatment [103]. Patel and colleagues demonstrated that Lactobacillus acidophilus pretreatment decreased COX-2 expression in catla thymus macrophages compared to Aeromonas hydrophila and co-stimulated macrophages [104].…”
Section: Modes Of Action Of Probiotic Bacteria In Antioxidationmentioning
confidence: 99%